1982
DOI: 10.1071/mf9821083
|View full text |Cite
|
Sign up to set email alerts
|

Macrobenthos of the cooling watre discharge canal of the Gladstone Power Station , Queensland

Abstract: Quantitative sampling of the macrobenthos of the cooling water discharge canal of the Gladstone Power Station has been conducted monthly from September 1976 to July 1980 (sampling times 1-47), to provide information on (i) the effects of an initially small but increasing thermal discharge on this biota, and (ii) the likely effects that could be expected to occur in the Calliope River, which will ultimately receive a 65-m3 s-1 thermal discharge with a maximum temperature differential of 8.2� C when the power st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1985
1985
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Saenger et al 1982); however, we discount this possibility because Thomas et al (1986) found no association between sediment type and distance from the source of thermal discharge in 1982, which was after the flow rate was increased with the further development of the power station.…”
Section: Indirect Environmental Effects On the Distribution And Abundmentioning
confidence: 89%
“…Saenger et al 1982); however, we discount this possibility because Thomas et al (1986) found no association between sediment type and distance from the source of thermal discharge in 1982, which was after the flow rate was increased with the further development of the power station.…”
Section: Indirect Environmental Effects On the Distribution And Abundmentioning
confidence: 89%
“…Changes to the coastline since the 1940s have included the reclamation or degradation of over 650 ha of mangroves and 990 ha of saltmarsh (QDEH, 1994). Localised changes to water quality and the estuarine biota have also been documented (Saenger et al, 1982). If estuarine communities are to be protected it is necessary that they are adequately documented and their conservation values assessed.…”
Section: Discussionmentioning
confidence: 99%
“…Scientists can also monopolize on already existing warm water effluents, such as emission of heated cooling water from power plants (e.g., [44][45][46][47][48][49]). If information on base-line levels is available from surveys conducted before construction, the effects of the temperature increase can be evaluated based on comparisons with more current situations as estimated from monitoring programs of recipient areas [49].…”
Section: Experimental Temperature Manipulation In the Wildmentioning
confidence: 99%